2009
DOI: 10.1002/pola.23670
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel fluorinated hyperbranched polyimides with excellent optical properties

Abstract: Novel anhydride‐terminated fluorinated hyperbranched polyimides (FHBPIs) were successfully prepared by condensation of a triamine monomer, 1,3,5‐tris(2‐trifluoromethyl‐4‐aminopheoxy) benzene (TFAPOB), and various aromatic dianhydride monomers with different linear length. UV–vis spectra indicate high optical transparency of FHBPI films with a UV–vis absorption edge of 350–395 nm. FHBPIs show increased mechanical properties with the linear length of dianhydride monomer. Young's moduli of FHBPI range from 2.37 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 98 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…The AB 2 monomers self-condensed to form different hb-PAEKs and the T g was 175, 197, or 215 C, depending on whether the repeat unit structure contained biphenyl, terphenyl, or quadriphenyl units in the polymer backbone. C, which was higher than the previously reported T g by Miller et al (140)(141)(142)(143) C) [63]. The hb homopolymer showed a bimodal molecular weight distribution that was also observed for other related linear hb systems.…”
Section: Hyperbranched Poly(aryl Ether)ssupporting
confidence: 59%
See 2 more Smart Citations
“…The AB 2 monomers self-condensed to form different hb-PAEKs and the T g was 175, 197, or 215 C, depending on whether the repeat unit structure contained biphenyl, terphenyl, or quadriphenyl units in the polymer backbone. C, which was higher than the previously reported T g by Miller et al (140)(141)(142)(143) C) [63]. The hb homopolymer showed a bimodal molecular weight distribution that was also observed for other related linear hb systems.…”
Section: Hyperbranched Poly(aryl Ether)ssupporting
confidence: 59%
“…The authors observed that hb-PI showed a birefringence as low as 0.002 at 650 nm, which was attributed to the presence of triamine monomers that reduced the orientation of the bonds in the polymer backbone and thereby reduced the birefringence. Liu et al [140] used a nonideal A 2 + B 3 polymerization approach to obtain fluorinated hb-PIs based on TFAPOB. A series of aromatic ether dianhydride monomers with different flexible linear lengths were used to overcome the poor mechanical properties of globular branched macromolecules.…”
Section: Hyperbranched Polyimidesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were first developed as industrial pigments, and have been diversely applied in various fields including chemical sensors, solar cells, catalysis, liquid crystals, and photodynamic therapy (PDT), 2-7 due to their stability, diverse coordination properties and optical properties. [14][15][16][17][18] Recently, our group have explored several PAEKs which contained metallophthalocyanine, here, we prepared a hyperbranched polyimide end-capped with metallophthalocyanine. [9][10][11][12] However, it is difficult for most phthalocyanine compounds to dissolve and to melt, which results in the restriction in their applications.…”
Section: Introductionmentioning
confidence: 99%
“…The important properties of flexible substrates are mechanical flexibility, thermal stability, optical transparency, and gas barrier properties. [34][35][36] Generally, typical materials for flexible substrates are polymer-based solid materials such as polyethylene terephthalate, 34 polyethylene naphthalate, 35 and PI. 36 Exceptionally, thin glass (thickness =~100 μm) has been used for flexible substrates, 37 however such thin glass (to the best of our knowledge) is still brittle under some forms of mechanical deformation.…”
Section: Research At Unist Display Centermentioning
confidence: 99%